2022
DOI: 10.1136/bmjopen-2021-058361
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of patients and health care professionals on the quality of telephone follow-up care during the COVID-19 pandemic: a large qualitative study in a multidisciplinary academic setting

Abstract: ObjectiveTo evaluate the perceived quality of follow-up telephone consultations (TCs) from the perspective of patients and healthcare professionals (HCPs) of multiple medical disciplines during the COVID-19 pandemic.DesignA qualitative study using semi-structured interviews and reflexive thematic analysis.SettingSeven medical disciplines (general dermatology, dermato-oncology, head and neck oncology, internal medicine, medical oncology, gynaecological oncology and surgical oncology) at a large university hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…In this study, most patients were worried about the accuracy of their health assessment in the absence of physical examinations and nonverbal communication. 17 It suggests a general feeling that quality of care is reduced when delivered remotely.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, most patients were worried about the accuracy of their health assessment in the absence of physical examinations and nonverbal communication. 17 It suggests a general feeling that quality of care is reduced when delivered remotely.…”
Section: Discussionmentioning
confidence: 99%
“…( 12) Furthermore, a lack of physical examination of oncology patients may result in patient perceptions of reduced quality of care and fears of inaccurate assessment of wellbeing. (13) In Australia, approximately 90% of Medicare Bene ts Schedule (health services subsidised by the Australian Government) telehealth consultations were conducted by telephone between 2021 and 2022, highlighting the limited uptake of videoconferencing as a platform for remote consultations. ( 12) Previous studies have proposed that videoconferencing be used in conjunction with consultations conducted via telephone to allow clinicians to recognise patient expressions and cues.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in outpatient follow-up visits was the most prevalent treatment modification in the early phase of the pandemic ( Powis et al, 2021 ), accompanied by a rapid introduction of digital communication ( de Joode et al, 2020 ; Powis et al, 2021 ). The shift to digital communication has been heralded as a ‘silver lining’ for cancer care ( Lombe et al, 2021 ), and welcomed by some patients ( Hasson et al, 2021 ; van Erkel et al, 2022 ). However, this and other studies have demonstrated that some cancer patients are less satisfied with emotional support during telephone consultations ( Bultz and Watson, 2021 ; Gotlib Conn et al, 2021 ; Kilgour et al, 2021 ; Page et al, 2022 ), find it less personal ( Zomerdijk et al, 2021 ) and are more likely to forget to ask questions ( Gotlib Conn et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%